2012
DOI: 10.1093/intqhc/mzs043
|View full text |Cite
|
Sign up to set email alerts
|

Using a knowledge translation framework to implement asthma clinical practice guidelines in primary care

Abstract: Quality problemInternational guidelines establish evidence-based standards for asthma care; however, recommendations are often not implemented and many patients do not meet control targets.Initial assessmentRegional pilot data demonstrated a knowledge-to-practice gap.Choice of solutionsWe engineered health system change in a multi-step approach described by the Canadian Institutes of Health Research knowledge translation framework.ImplementationKnowledge translation occurred at multiple levels: patient, practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The literature also reports 70,71 on the small number of studies applying a theoretical background and encourages its use tailored to the setting and to the aim of intervention. 70 Economic evaluation of guideline implementation interventions is rarely reported, 12,13 our hits demonstrating no exception: three studies 31,35,41 presented cost-benefit or cost-effectiveness information. This indicates that research should focus on adding this essential aspect in favour of comprehensive comparability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also reports 70,71 on the small number of studies applying a theoretical background and encourages its use tailored to the setting and to the aim of intervention. 70 Economic evaluation of guideline implementation interventions is rarely reported, 12,13 our hits demonstrating no exception: three studies 31,35,41 presented cost-benefit or cost-effectiveness information. This indicates that research should focus on adding this essential aspect in favour of comprehensive comparability.…”
Section: Discussionmentioning
confidence: 99%
“…34,40,44,47,54,57,58 (3) Seven studies used diverse single approaches including audit, 25,31,43 motivational interview, 53 reminder 26,32 and patient-mediated intervention. 41 Multifaceted interventions mainly applied a combination of two methods, one of them a kind of training approach, extended by a second methodologically different method. From these, (4) the combination of educational meeting and audit/feedback was the most frequent with four studies.…”
Section: Methods Of Interventionmentioning
confidence: 99%
“…65 Reduction in urgent care and emergency room visits for children with asthma has been seen from asthma care guideline use. 66 Protocol adherence for seizure management in the emergency department and pediatric intensive care unit also has been shown to be beneficial for patients. 67,68 Practice guidelines need to be reviewed and updated.…”
Section: Guideline Utilizationmentioning
confidence: 99%
“…A convenience sample of subjects recruited from the Primary Care Asthma Program in Windsor, Ontario, was used. This population has been described previously (8). Adults (>18 years of age) with a physician diagnosis of asthma who reported symptom worsening with exposure to air pollution were enrolled.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…It is a communication tool that supports patients in the assessment of asthma control and directs management decisions that occur between regular clinic visits. In the context of regular clinical review, the written asthma action plan has been demonstrated to be efficacious in multiple randomized controlled trials and demonstrated to be effective as a component of care in community asthma programs (7)(8)(9).…”
mentioning
confidence: 99%